Investment timing and quantity under ambiguity and business cycles - Wenhe Song; Shou Chen (Journal of Applied Economics, 2024)
We extend a dynamic investment model that captures the conjoint effect of ambiguity and the business cycle on the investment threshold and endogenous investment quantity choice. This paper focuses on investment strategies under the combined effects of ambiguity and business cycles. We reveal through quantitative results that the risk effect and ambiguity effect have opposite effects on optimal investment threshold and optimal investment quantity, and the risk effect dominates the ambiguity effect. The transfer intensity coefficient from a boom period to a recession period and the risk effect are opposite effects, and the transfer intensity coefficient effect dominates the risk effect. Moreover, the transfer intensity coefficient from a boom period to a recession period has a synergistic effect with the ambiguity effect. Meanwhile, the transfer intensity coefficient from recession to boom is the opposite effect of risk and a synergistic effect with ambiguity.
Keywords: 330; Ambiguity; business cycle; endogenous quantity; investment timing